Generation of ultra-high bandwidth chaos in EDFRL using Moiré grating - S. Zafar Ali; M.K. Islam; D.A. Mazhar (Results in Optics, 2023)
This milestone work overcomes the lower bandwidth limitation of Erbium Doped Fiber Laser (EDFRL) by inserting a Moiré Grating in the laser loop, with closely spaced wavelengths so that beating of wavelengths produces a very high bandwidth pulsed chaos. The chaos bandwidth variation is studied with respect to three parameters i.e., wavelength spacing, fiber Bragg grating bandwidth and fiber nonlinearity. The high bandwidth chaos can be produced with rich and flatter spectral content by controlling the said parameters in a narrow range studied in this work. The chaotic pulses become narrow in pulse width, closely spaced in time and more dynamic in amplitude. The Lyapunov Exponent increases as the chaos becomes more unpredictable. The EDRFL, known for more control parameters can be deployed in higher bandwidth chaos generation applications besides semiconductor laser.